2021
DOI: 10.1007/s13201-021-01459-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of water use behavior and calculation of water footprint: a case study

Abstract: This article adds to the literature on the investigation of water use behavior of people under their daily routines. A self-administrated survey of water users was conducted for both graduate and undergraduate students at Boğaziçi University, Turkey in 2019. This study quantifies and maps the water footprint (WF) of Boğaziçi University (BU). It reports preferences of students and personnel in terms of indoor water use, outdoor water use, and virtual water use such as transportation, shopping, and dietary prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The Water-Energy-Food nexus (WEF) model explored the relationship between water demand, energy requirements and food supplies (Entrena et al, 2023). For statistical analysis, the IBM SPSS Statistics Data Editor 25 allowed linear regressions to be performed to determine the Total Water Footprint (Okutan & Akkoyunlu, 2021). The WEF method also facilitated comparisons between blue and green water footprints (Su, Zheng & Llao, 2022).…”
Section: Content Resultsmentioning
confidence: 99%
“…The Water-Energy-Food nexus (WEF) model explored the relationship between water demand, energy requirements and food supplies (Entrena et al, 2023). For statistical analysis, the IBM SPSS Statistics Data Editor 25 allowed linear regressions to be performed to determine the Total Water Footprint (Okutan & Akkoyunlu, 2021). The WEF method also facilitated comparisons between blue and green water footprints (Su, Zheng & Llao, 2022).…”
Section: Content Resultsmentioning
confidence: 99%
“…It is seen that students have higher CFP and WFP values compared to the national diet before education. A study evaluating the diet-related WFP of university students in Turkey found it to be 3901 L/day [ 65 ]. It is seen that university students have more negative effects on the environment than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…and building types. The figures should also vary across regions/provinces; however, the water demand for toilet flushing in urban can be assumed as 18-24 lpcd, considering the average needs of flushing reservoir volumes (DIN 1989;Belmeziti et al 2013;Okutan & Akkoyunlu 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This study assumes that the water demand for toilet flushing is the same for all urban areas in all provinces in Türkiye. Thus, the water demand for toilet flushing is 24 lpcd in residential buildings (DIN 1989;Okutan & Akkoyunlu 2021). That sums to a daily water demand of 144 L for a family of six members, monthly water demand of 4.32 m 3 , and annual water demand of 53 m 3 in the residential buildings.…”
Section: Calculation Of Water Demand and Potential Rainwater Harvestingmentioning
confidence: 99%